Effect of basalt fiber content on mechanical properties of hydrophobic mortar - Yunfeng Li; Qing Wang; Xu Zheng; Rui Zhang; Ning Wang (Scientific Reports)
Abstract The addition of a hydrophobic agent to fiber concrete can realize the overall hydrophobic of the material, which can prevent damage to cementing material due to its porous and hydrophilic properties. However, the impact of varying fiber content on the mechanical properties of these materials remains unclear, limiting their large-scale application in extreme environments. Mechanical experiments were conducted to obtain the material’s elastic modulus, compressive strength, and Poisson’s ratio, aiming to explore the reinforcing effect and mechanism of fibers on mechanical properties. The mechanical parameters of hydrophobic basalt fiber cement-based materials with different fiber content were calculated by Mori–Tanaka homogenization theory calculation and mesoscopic numerical simulation. Scanning electron microscopy results displayed the binding between the fiber and the gelling material was good, there was no obvious alkali-silicon reaction damage, and the homogeneity analysis could be carried out. When the fiber content was below 1.5%, there was good agreement among the experimental, finite element, and numerical simulation data. When the fiber content was 2%, deviations in numerical values occurred due to fiber agglomeration failure. These findings provided a foundation for optimizing fiber content in hydrophobic basalt fiber cement-based materials, supporting their broader application in durable concrete structures.